Potensi Hasil dan Toleransi Galur-galur Inbrida Sorgum pada Tanah dengan Hara Fosfor Rendah - Momongan, Jorex Daniel; Trikoesoemaningtyas, Trikoesoemaningtyas; Wirnas, Desta; Sopandie, dan Didy (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Sorghum development in Indonesia is directed towards cultivation in dryland and acid soil with low P availability. This research was aimed to obtain information on the performance of sorghum traits for selection in P deficient environment at early vegetative phase (3 weeks after planting), agronomic and yield potential traits in both P sufficient and P deficient environments, also to select high productivity sorghum genotypes which could tolerate P deficiency. The genetic materials used were 19 F7 recombinant inbred lines from a cross of B69 x Numbu developed under optimum condition (indirect breeding) by single seed decent. Variety Numbu and B69 used as checks. This research was conducted at The Indonesian Center for Biotechnology and Agriculture Plant Genetic Resources experimental field, Bogor, from May to September 2017. The experiment used a randomized complete block design with 3 replicates. The results showed that agronomic and yield traits varied among inbred lines under low P condition and optimum P condition. Adaptive lines showed better growth and yield compared to sensitive ones under low P condition. Plant height, panicle weight, and grain weight per panicle had high estimates of broad sense heritability. Selection based on stress tolerance index was able to identify inbred lines 286-6, 115-9, 114-7, 331-8, 170-9, 151-8, 104-7, 413-7, 68-5, 315-6, and 341-7 as tolerant to low P condition.Keywords: heritability, indirect breeding, optimum P condition, stress tolerance index